(3Mb GdQLhY ai GdJYGbO hab bGfhf MeGjI GdeSJgdc GdeUQi (B181 (3dSfI(B2018: s (3OQGSI ebGQfI (B/ s - (3eMeO eMehO MSjf eDefs; (3LGHQ eMLhH Ydis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3Mb GdQLhY ai GdJYGbO (B((3hab bGfhf MeGjI GdeSJgdc GdeUQi Qbe (B181(3dSfI (B2018). (3CQOJ ef NdGd gPg GdOQGSI EdbGA GdVhA Ydi Mb QLhY GdeSJgdc ai GdJYGbO; aJhUdJ Edi chfg QNUI JTQjYjI efMJ ddeSJgdc ddJCcO ef EcJeGd h fVL QVGFg(B: (3h Ohf Cf jJhba EYeGdgG Ydi EQGOI GdWQa GdBNQ ai GdYbO(B: (3h gPG GdMb dg NUGFU JejRg(B: (3h eHQQGJ bGfhfjI hELJeGYjI h CNdGbjI OGaYI Edi VQhQI EbQGQg fUG JTQjYjkG(B: (3h GfJgjJ HHjGf TQhWg h VhGHW EYeGdg(B: (3h cPdc BKGQg h WQb GfbVGFg; cd Pdc hab bGfhf MeGjI GdeSJgdc GdeUQi Qbe (B181(3dSfI (B2018: (3eY ebGQfI cd eG WQMfGg WhGd UaMGJ GdHMK HbGfhf MeGjI GdeSJgdc GdaQfSi GdUGOQ ai (B1(3jhdjh dSfI (B2016s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2020s
(3HHdjhLQGajG(B: (3UaMGJ (B213-222s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdeSJgdcs; (3GdQLhY aj GdJYGbOs; (3YbO GdGSJgdGcs; (3QNUI JTQjYjIs; (3bGfhf MeGjI GdeSJgdc GdaQfSjs; (3TQW GdJLQHIs; (3GdYbO ZjQ GddGRes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs